Factors influencing the occurrence of Fusarium mycotoxins in the grain of winter wheat - Aleksandrowicz, Edyta (Polish Journal of Agronomy, 2020)
Fusarium mycotoxins are secondary metabolites, bio-synthesized by filamentous fungi of the genus Fusarium, which, due to their diverse toxicity and difficulty in their removal from food and animal feeds, are the subject of research by scientists around the world. The most important mycotoxins found in wheat are: deoxynivalenol (DON), zearalenone (ZEN), and the T-2 and HT-2 toxins. Bearing consumer safety in mind, the levels of these substances in grain, food and animal feeds are regulated by law. In order to meet the health safety requirements imposed on grain, it is important to minimise the risk of fungal infection at individ-ual production stages. Weather conditions are the most important factor influencing the development of fungi and the accumula-tion of mycotoxins in grain. High temperature, combined with rainfall, are factors favouring the spread of fungal spores. Apart from weather conditions, individual elements of the production technology, such as appropriate variety selection, soil cultivation method, preceding crop, use of fungicides, and fertilization may reduce the quantity of mycotoxins in grain. In the conditions of the emerging climatic changes, favouring the development of fun-gal diseases, creating wheat varieties resistant to fungal diseases is a considerable challenge. Acquiring more in-depth knowledge on the relationship between the phenotypic features of a wheat variety and mycotoxin content would be helpful. This work is of review character and aims to indicate the basic factors influenc-ing the production of fusarium mycotoxins in winter wheat grain. The focus was placed on factors independent of human activity (weather conditions) and on individual elements of cultivation technology.